2021
DOI: 10.1098/rsos.202039
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the classification of squamate adhesive setae: historical, morphological and functional perspectives

Abstract: Research on gecko-based adhesion has become a truly interdisciplinary endeavour, encompassing many disciplines within the natural and physical sciences. Gecko adhesion occurs by the induction of van der Waals intermolecular (and possibly other) forces between substrata and integumentary filaments (setae) terminating in at least one spatulate tip. Gecko setae have increasingly been idealized as structures with uniform dimensions and a particular branching pattern. Approaches to developing synthetic simulacra ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…In addition to the well-known adhesive setae, the toepads of geckos also possess epidermal outgrowths at their bases [51,52]. For simplicity, we geometrically divided a toepad into a region covered by setae and a region that has no setae (i.e.…”
Section: Animal Running Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the well-known adhesive setae, the toepads of geckos also possess epidermal outgrowths at their bases [51,52]. For simplicity, we geometrically divided a toepad into a region covered by setae and a region that has no setae (i.e.…”
Section: Animal Running Experimentsmentioning
confidence: 99%
“…Presumably, the directionally arranged non-adhesive scales make the bases of the toes function more like a ratchet (figure 2(a) insets), producing anisotropic types of friction. Moreover, the bases of the toes might contain some micro-outgrowths that can also lead to directional forces [52], therefore also contributing to the anisotropic friction.…”
Section: Scales Add Anisotropic Friction To Toe Adhesionmentioning
confidence: 99%
“…Explorative visual assessment showed that the anole skin surface is covered by fine structures of varying height consisting of two distinct lengths: short, tapered outgrowths (which we call here ‘spinules’) and elongated outgrowths with a slightly hooked end (which we call here ‘spines’). Terminology classification is consistent with Garner and Russell (2021) . The following variables of the surface structure of anole skin were extracted from the SEM images and quantified using ImageJ ( Abràmof et al, 2005 ): (1) scale area (mm 2 ) – the area of 10 scales per skin sample; (2) structure density – the number of hair-like structures (irrespective of length category) per 25 µm 2 , assessed on average 5 times (each from a different location on the skin) per skin sample; (3) structure length (µm) – the length of the hair-like structures from the base to the very tip (15 spines and 15 spinules measured per skin sample) and; (4) structure spacing (µm) – the distance between the bases of two adjacent structures (irrespective of length category), measured 10 times per skin sample.…”
Section: Methodsmentioning
confidence: 78%
“…For some aquatic organisms, many multi-level structures have been found on the microscale, and even nanoscale, in their hair structures, which may add important weight to the significant enhancement of their attachment capacity. Unlike multi-level hair-like structures of some terrestrial organisms such as geckos and beetles, most of the hair-like structures of aquatic attachment organisms do not have a spoon-like end structure that can generate van der Waals forces [ 86 , 87 , 88 , 89 ]. However, the attachment capacity of aquatic organisms is not affected by the combined action of multi-level hairs.…”
Section: Non-smooth Structural Morphologies and Attachment Mechanisms...mentioning
confidence: 99%